Sosialisasi penerapan Smart e-Monitoring untuk pasien Covid-19 berbasis IoT di STIPARK NTB - Indra Gunawan; Nurhidayati Nurhidayati; Lalu Kerta Wijaya; Farid Wajdi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
The Merdeka Campus Competition Program, held by the Ministry of Education, Culture, Research, and Technology, is a financing program that aims to facilitate, encourage, and accelerate the transformation of higher education institutions. Informatics Engineering Study Program, Hamzanwadi University, as one of the universities that received the grant, developed an Internet of Things-based application to monitor the progress of Covid-19 patients who are self-isolating called SMART e-MONITORING. Therefore, this activity aims to socialize the Smart e-Monitoring application at STIPARK NTB as partners. This activity was held over four months. It’s were starting from product presentations to system testing and product launching. The activity results show that the developed application can run well and display the patient's condition in real-time. The recorded data include body temperature data, oxygen levels (SPO2), and heart rate (BPM). This data is used to facilitate the handling of self-isolated patients in real-time and without direct contact with Covid-19 patients.